Enfermedades dermatológicas causadas por fungicidas de las bananeras en los alumnos de las escuelas marginales de Machala. 2014 casos y controles. - Román Relica, Laura Geanella (2015)
The El Oro province is predominantly agricultural where banana monoculture, which is one of the main economic engines, supported by public policies aerial spraying of pesticides aimed at improving production in the approximately 63.883 existing 2014 acres predominates, without worry about the harmful effects these chemicals can cause to the environment and its inhabitants. Therefore they are trying to demonstrate these effects on the health of people who are exposed we set as an objective: Determine dermatological diseases caused by fungicides in banana students of marginal schools.